The Material Family - Torrant, Julie P.; SpringerLink (Online service) (Rotterdam : SensePublishers : Imprint: SensePublishers, 2011)
The Material Family is a bold new reading of the family, focusing on (3z(Bnew(3y (Bor (3z(Bpost-nuclear,(3y z(Bflexible(3y (Bfamily forms such as gay family, divorce-extended family, and transnational family. Reading across a range of texts from high theory to literature and popular films, the book crosses disciplinary boundaries to offer a highly innovative and dynamic approach to changes in gender and other family relations. Unlike most books in the fields of cultural and family studies, The Material Family provides an historical and materialist argument connecting the changes within family to underlying shifts in material, labor relations in global capitalism. The (3z(Bpost-nuclear(3y (Bfamily is not only an affective space, Torrant argues, but one whose affects are themselves fundamentally shaped by class. The Material Family is a must-read for anyone who wants to venture beyond the surfaces of family life to the deeper-lying relations that have made the family and its new forms among the most important spaces of social life. Its readers will include not only students and researchers in the fields of education, cultural theory and cultural studies, women$1 (Bs studies, sociology, and anthropology, but also general readers interested in understanding contemporary families and their struggles.s
Keywords: Education; Education; Education (general).